In similarity to Latin America. (Journal of Parents and Teachers, 2014)
The following article tells the experience lived by some young people through the programme "Jóvenes como tú"; of the NGO Entreculturas. During the experience, young people from both sides of the Atlantic were encouraged to look for similarities rather than differences between them. We invite you to read on to discover the steps to follow.
Keywords: English; Spanish